Ethnic fashion: its problem around cultural appropriation in Peru - Amoretti Lamadrid, Elsa Maria (2023)
Ethnic fashion can be problematic due to the very fine line that exists between the inspiration that can be used in the creation of designs and cultural appropriation. There are innumerable cases in which big brands, usually international, use typical designs of a culture belonging to a minority without any type of authorization from these people.This non-consensual use comes to generate harm to the member of these communities, both economically and socially, which is why some countries, in order to reduce these damages, have regulated this issue. Thus, this research seeks to develop key subjects such as ethnic fashion and cultural appropriation, as well as to analyze the current Peruvian situation regarding cultural appropriation.